Implementation of Energy Awareness and Environmental Education Programs in Hungarian Higher Education: Evaluation of a Pilot Program - Kozma, Gábor; Nemeskéri, Zsolt; Pongrácz, Attila; Zádori, Iván (Acta Cultura et Paedagogicae, 2023)
Our study aims to evaluate the pilot training conducted in the framework of the project "Environmental education and sustainability - implementation of energy awareness and environmental education programs in Hungarian higher education" with the support of the Hungarian Energy and Public Utilities Regulatory Office. Our study includes the presentation of the four higher education institutions participating in the pilot program, the methodology of the research and the summary of the results obtained. An important result of the research is that among the students and teachers of the higher education institutions participating in the pilot project, interest in and commitment to environmental education and sustainability can be traced. The results highlight that current and future teachers are trying to do as much as possible in their respective fields so that the next generation will be prepared to deal with the currently visible and expected sustainability challenges.